HEALTH RISK ASSESSMENT DUE TO CLEAN WATER USAGE (CASE STUDY: CIPARAY, MARGAASIH AND DAYEUHKOLOT SUB-DISTRICT, BANDUNG DISTRICT) - Hasanawi, Adib
Population growth affects the need for water which increases in quantity followed by increase in quality and continuity The decline in the quality of clean water occurred in Bandung District, especially in three areas, namely Ciparay, Dayeuhkolot and Margaasih sub-districts. In addition, the shift in the pattern of drinking water source to refill drinking water in the area has the potential for contamination. Therefore, a public health risk assessment is carried out due to the use of clean water for drinking water and sanitation hygiene. Risk characterization is carried out by quantitative methods of calculating the value of the Hazard Quotient (HQ), Hazard Index (HI), and Excess Cancer Risk (ECR) with Monte Carlo simulation analysis. The results showed that the quality of refill drinking water exceeds the drinking water quality standard of Permenkes 492/2010 on the parameters of E. coli, total coliform, and heavy metals (Fe, Al, Se) and the quality for sanitary hygiene water exceeds the quality standard of Permenkes 32/2017 on parameter E. Coli, Total Coliform, heavy metals (Cr, Mn, and Hg). Dermal and oral exposure due to the use of clean water showed a non-carcinogenic risk (HI> 1) in 4 categories which were for, adults - Ciparay (1.12), children - Ciparay (1.45), children - Margaasih (1.13) and children - Dayeuhkolot (1.24). Carcinogenic risk also occured (ECR >1x10-4), namely 1.05 x 10-4 in the adult category in Ciparay District as agricultural area. Efforts to process clean water and evaluate the quality of clean water need to be carried out by the government and land use masterplan are also needed to conduct for reducing public health risks.